2001
DOI: 10.1038/sj.ejcn.1601232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary quality in relationship to nutritional and lifestyle factors in elderly people of the US Framingham Heart Study and the European SENECA study

Abstract: Objective: To evaluate dietary quality of European and American elderly subjects using different derivatives of dietary patterns (dietary scores and clusters) and to investigate the relationship of these approaches to nutritional and lifestyle factors. Design: Data from the cross-sectional SENECA baseline study and Framingham Heart Study (original cohort and offspring) were used for data analysis. Food intake data were summarised into dietary clusters and into dietary scores (Healthy Diet Indicator and Mediter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
2
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 38 publications
7
60
2
4
Order By: Relevance
“…Evidence of inadequate dietary intakes of vitamin A, vitamin E and folates is lacking and the biochemical indicators suggest that the circulating levels of vitamins are in the cutoff point of normality. These findings are in disagreement with some literature data on similarly aged Europeans who have inadequate vitamin A and folate intake and limiting vitamin nutritional status (Euronut SENECA investigators, 1991;Maiani et al, 1992;Hallfrish et al, 1994;Haveman-Nies et al, 2001;Pirlich and Lochs, 2001;Ferry et al, 2005;Tur et al, 2005). In our study, no vitamin deficiencies are observed in all age groups, probably because of the specific selection criteria used for the enrollment of apparently healthy free-living volunteers (Table 1).…”
Section: Discussioncontrasting
confidence: 57%
“…Evidence of inadequate dietary intakes of vitamin A, vitamin E and folates is lacking and the biochemical indicators suggest that the circulating levels of vitamins are in the cutoff point of normality. These findings are in disagreement with some literature data on similarly aged Europeans who have inadequate vitamin A and folate intake and limiting vitamin nutritional status (Euronut SENECA investigators, 1991;Maiani et al, 1992;Hallfrish et al, 1994;Haveman-Nies et al, 2001;Pirlich and Lochs, 2001;Ferry et al, 2005;Tur et al, 2005). In our study, no vitamin deficiencies are observed in all age groups, probably because of the specific selection criteria used for the enrollment of apparently healthy free-living volunteers (Table 1).…”
Section: Discussioncontrasting
confidence: 57%
“…A high consumption of both fish and grain was characteristic for Southern centres participating to the European SENECA (Survey in Europe on Nutrition and the Elderly: a Concerted Action) study (Haveman-Nies et al, 2001). This dietary pattern was also associated with use of wine and high consumption of fruit but not vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have tried to characterize fish consumers in Western countries (Burger et al, 2002;Welch et al, 2002;Davey et al, 2003) and very few were based on representative samples of elderly community dwellers (Haveman-Nies et al, 2001). Fish consumption is generally considered among other dietary patterns (van Dam et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It intends to measure adherence to a predefined (healthy) diet (5) . Thus far, several dietary scores have been related to positive health outcomes (6)(7)(8) . Dietary scores have the advantage of taking into account the complex interactions and cumulative effects of multiple foods and nutrients within the diet; consequently the health-related effects may be larger and easier to detect.…”
mentioning
confidence: 99%